2000
DOI: 10.1097/00003246-200005000-00051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuromuscular blockade on oxygen consumption and energy expenditure in sedated, mechanically ventilated children

Abstract: NMB significantly reduces oxygen consumption and energy expenditure in critically ill children who are sedated and mechanically ventilated; the degree of reduction is small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 15 publications
2
46
1
4
Order By: Relevance
“…We observed a number of factors, as seen in We also acknowledge a final limitation of our study being that neither the individual's race nor his or her sedation level was taken into account, affecting the resting energy state of our population. 34,35 Our study demonstrates that a statistically …”
Section: Discussionmentioning
confidence: 55%
“…We observed a number of factors, as seen in We also acknowledge a final limitation of our study being that neither the individual's race nor his or her sedation level was taken into account, affecting the resting energy state of our population. 34,35 Our study demonstrates that a statistically …”
Section: Discussionmentioning
confidence: 55%
“…NMB ajanların ET ve VO 2 üzerine etkisini indirekt kalorimetri yöntemi kullanarak araştıran bir çalışmada pediatrik yoğun bakımda mekanik ventilatör desteğinde 20 hasta çalışmaya alınmıştır (11) . Midazolam ve/veya fentanil ile sedatize izlenen hastalarda NMB uygulanmasından sonra VO2'de %8,7 , ET'de %10,3'lük (p<0,05) bir azalma saptanmıştır.…”
Section: Discussionunclassified
“…However, Muldoon and Theye [28] reported already in 1969 that whole-body VO 2 was decreased in dogs paralyzed with d-tubocurarine, and some clinical studies investigating the effects of NMB on VO 2 reported a reduction of total-body VO 2 and energy expenditure by NMB in sedated and mechanically ventilated children [8] and in adults suffering acute respiratory failure [7], severe cerebral trauma [29] or burn injuries [30]. Inconsistently, other investigators found no effects of NMB on VO 2 in deeply sedated intensive care unit patients (Ramsay score 5) [31] or in anesthetized patients undergoing cardiac surgery [32].…”
Section: Discussionmentioning
confidence: 99%
“…While NMB has been demonstrated to decrease total body energy expenditure and VO 2 [7,8], to date, a potential influence on anemia tolerance has not been investigated. We hypothesized that NMB should increase the tolerance of acute normovolemic anemia – reflected by a significantly lower value of Hb crit and a higher volume of blood allowed to be exchanged for hydroxyethyl starch (HES).…”
Section: Introductionmentioning
confidence: 99%